Cytokine serum levels remain unchanged during lithium augmentation of antidepressants in major depression. (January 2018) - Ricken, Roland; Busche, Marlene; Schlattmann, Peter; Himmerich, Hubertus; Bopp, Sandra; Bschor, Tom; Richter, Christoph; Stamm, Thomas J.; Heinz, Andreas; Hellweg, Rainer; Lang, Undine E.; Adli, Mazda
Abstract: Lithium augmentation (LA) of antidepressants is a first-line therapy in treatment-resistant depression. Immunomodulatory effects of lithium have been described. The cytokine hypothesis of depression postulates that cytokines play a key role in the pathophysiology of depression. Concordantly, it has been shown that proinflammatory cytokine serum levels decrease during antidepressant treatment. The aim of this study was to investigate changes in cytokine serum levels during LA. Serum concentrations of the cytokines interleukin (IL)-2, IL-4, IL-6, IL-8, IL-10, tumour necrosis factor alpha, interferon-gamma, granulocyte and monocyte colony stimulating factor were measured in a total of 95 acutely depressed patients before and after four weeks of LA. Changes in cytokine levels were corrected for the confounding factors severity of depression, treatment response, lithium serum level, gender, age and body mass index in a linear mixed-model analysis. We did not find a significant change in any of the measured cytokine serum levels during LA (p > 0.05). In conclusion, our study does not support the role of cytokine serum levels as a state marker in treatment of depression with LA. Highlights: First study investigating cytokine serum levels during lithium augmentation (LA) . IL-2, -4, -6, -8, -10, TNF-α, IFN-γ and GMCSF measured in a prospective study, n = 95 . No significant change was found in any of the measured cytokine levels during LA . Results do not support the role of cytokines as a state marker in treatment with LA .